Short communicationsCoronary accordion effect mimicking coronary dissection - Cagliyan, Caglar Emre; Balli, Mehmet; Akilli, Rabia Eker; Tekin, Kamuran; Cayli, Murat (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
The coronary “accordion” effect is a rare pseudo-complication of percutaneous coronary intervention (PCI). It is usually observed due to straightening and shortening of tortuous vessels with stiff guidewires during PCI. In this case report, we present an interesting case of the coronary accordion effect observed in a 52-year-old woman undergoing PCI.